2019
DOI: 10.1038/s41564-019-0480-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic combinations that exploit heteroresistance to multiple drugs effectively control infection

Abstract: Antibiotic resistant bacteria are a significant threat to human health, with one estimate suggesting they will cause 10 million worldwide deaths per year by 2050, surpassing deaths due to cancer 1. Since new antibiotic development can take a decade or longer, it is imperative to effectively use currently available drugs. Antibiotic combination therapy offers promise for treating highly resistant bacterial infections, but the factors governing the sporadic efficacy of such regimens have remained unclear. Dogma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 28 publications
3
92
0
2
Order By: Relevance
“…Treatment of the bacteria with MEM at 4,000 µg/L exhibited a bacteriostatic effect on 3 CRKP isolates and treatment of the bacteria with AMK at 8,000 µg/L inhibited the growth of 3 CRKP isolates. Our observed phenotype of the CRKP isolates was consistent with what has recently been reported in the United states, indicating the hetero-resistance of CRKP isolates to the drugs contributes to bacteriostatic effect and regrowth (Band et al, 2018(Band et al, , 2019. Therefore, combination therapy is needed not only to fight the multiple-drug resistant CRKP isolates but also to prevent the emergence of the resistance during the treatment.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Treatment of the bacteria with MEM at 4,000 µg/L exhibited a bacteriostatic effect on 3 CRKP isolates and treatment of the bacteria with AMK at 8,000 µg/L inhibited the growth of 3 CRKP isolates. Our observed phenotype of the CRKP isolates was consistent with what has recently been reported in the United states, indicating the hetero-resistance of CRKP isolates to the drugs contributes to bacteriostatic effect and regrowth (Band et al, 2018(Band et al, , 2019. Therefore, combination therapy is needed not only to fight the multiple-drug resistant CRKP isolates but also to prevent the emergence of the resistance during the treatment.…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported that the mortality rates can be as high as 40-50% in patients with CRKP infections (Patel et al, 2008). The pathogens often harbor multiple drug-resistant genes that cause the bacteria hetero-resistance to antibiotics in addition to β-bactams (Band et al, 2018(Band et al, , 2019, severely limiting alternative treatment options and increasing therapeutic cost (Huang et al, 2018;Santos and Secoli, 2019). The development of new antimicrobial agents to combat new CRKP isolates is extremely time-consuming, and therapeutic replacement with novel alternative agents may cause potential toxicities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the SE collection, only the S07 strain was susceptible to oxacillin (6 g/ml) in plate assays, despite the detection of mecA in the genome. Altogether, these results indicate that most of the SE strains (15) studied here are MRSE, identified by the presence of the mecA gene; any phenotypic inconsistencies could be due to lack of expression of the mecA, heteroresistance, or the limitation of the current antibiotic susceptibility testing methods (Band et al 2019;Harrison et al 2019;Nicoloff et al 2019).…”
Section: Survey Of Antibiotic Multidrug-resistant Intrahospital Staphmentioning
confidence: 56%
“…For example, the emergence of "superbugs" such as methicillin-resistant Staphylococcus aureus (MRSA) (Lakhundi and Zhang, 2018;Turner et al, 2019), vancomycin resistant Enterococcus (VRE) (Courvalin, 2006), MCR positive Enterobacteriaceae (Liu et al, 2016), and high-level tigecycline resistance in E. coli (He et al, 2019;Sun et al, 2019) is accelerating and resulting in the growing failure of antibiotic treatment. Alarmingly, except for genetically encoded antibiotic resistance (Blair et al, 2015) and antibiotic heteroresistance (a transient antibiotic resistance due to gene amplifications) (Band et al, 2019;Nicoloff et al, 2019), bacteria have evolved multi-approaches to withstand antibiotic therapy such as antibiotic tolerance (Dhar and Mckinney, 2007;Kim, 2007). This is a biology phenomenon that describes bacteria that are genetically susceptible, but phenotypically tolerant to antibiotic treatment (Brauner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%